Psychosocial Consequences of Caregiver Transitions for Maltreated Youth Entering Foster Care: The Moderating Impact of Community Violence Exposure - Garrido, Edward F. (2011)
Youth who experience a greater number of caregiver transitions during childhood are at risk for developing a host of psychosocial problems. Although researchers have examined individual-level factors that may moderate this association, no known studies have examined the impact of community-level factors. The current study investigated whether community violence exposure moderated the association between number of prior caregiver transitions and increases in levels of externalizing and internalizing problems for a sample of youth entering foster care. Participants included 156 youth (age 9 to 11 at first assessment) removed from their homes because of maltreatment. Youth provided reports of caregiver transitions and community violence exposure at baseline, and caregivers, teachers, and youth reported on externalizing and internalizing problems 18–22 months later. Results from hierarchical multiple regression analyses indicated that youth with a greater number of caregiver transitions and higher levels of community violence exposure evidenced significant increases in levels of psychosocial problems. The results of the study are discussed in terms of their implications for child welfare services.